Cymbopogon martinii essential oil and geraniol at noncytotoxic concentrations exerted immunomodulatory/anti-inflammatory effects in human monocytes - Murbach Teles Andrade, Bruna Fernanda [UNESP]; Conti, Bruno Jose [UNESP]; Santiago, Karina Basso [UNESP]; Fernandes Junior, Ary [UNESP]; Sforcin, Jose Mauricio [UNESP] (Wiley-Blackwell, 2014)
ObjectivesIn traditional medicine, plants have formed the basis of sophisticated systems that have been in existence for thousands of years and still provide mankind with new remedies. Cymbopogon martinii, known as palmarosa, has been used in aromatherapy as a skin tonic due to its antimicrobial properties. It has also used in Ayurvedic medicine for skin problems and to relieve nerve pain. The immunomodulatory action of C.martinii essential oil (EO) and geraniol was evaluated regarding the production of pro- and anti-inflammatory cytokines (tumour necrosis factor (TNF)- and IL-10, respectively) by human monocytes in vitro.MethodsMonocyte cultures were incubated with EO or geraniol. After 18h, cytotoxicity assays were performed using 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide method, and cytokine production was determined by ELISA.Key findingsThe variables showed no cytotoxic effects on monocytes. TNF- production was not affected by C.martinii and geraniol, and only the concentration of 5g/ml of C.martinii stimulated its production. On the other hand, all concentrations of C.martinii and geraniol increased IL-10 production by human monocytes.ConclusionsData showed that noncytotoxic concentrations of EO and geraniol exerted an anti-inflammatory action by increasing IL-10 production; moreover, geraniol seemed to be probably responsible for EO immunomodulatory activity in our assay condition.
Keywords: Cymbopogon martinii; cytokines; essential oil; geraniol; monocytes